2006
DOI: 10.1002/bip.20578
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crowding by dextrans and Ficolls on the rate of alkaline phosphatase–catalyzed hydrolysis: A size‐dependent investigation

Abstract: The cell cytosol is crowded with macromolecules such as proteins, nucleic acids, and membranes. The consequences of such crowding remain unclear. How is the rate of a typical enzymatic reaction, involving a freely diffusing enzyme and substrate, affected by the presence of macromolecules of different sizes, shapes, and concentrations? Here, we mimic the cytosolic crowding in vitro, using dextrans and Ficolls, for the first time in a variety of sizes ranging from 15 to 500 kDa, in a concentration range 0-30% w/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
75
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(95 citation statements)
references
References 26 publications
19
75
1
Order By: Relevance
“…In contrast, with small obstacles the effect of crowding is partially offset by enhancement of the enzyme activity owing to a caging effect, which results in a minor decrease in rate. However, both Homchaudhuri et al 38 and our results are in agreement in that, as stated by Minton et al 2,[8][9][10][11][12] , the excluded volume plays an important role in the enzymatic reactions that take place in macromolecular crowded media. We have found that, at least in the case of the hydrolysis of N-succinyl-L-phenyl-Ala-p-nitroanilide catalyzed by alpha-chymotrypsin, the total volume excluded by the crowding agents has a greater impact on the velocity of the reaction than the size of these agents.…”
Section: Resultssupporting
confidence: 94%
“…In contrast, with small obstacles the effect of crowding is partially offset by enhancement of the enzyme activity owing to a caging effect, which results in a minor decrease in rate. However, both Homchaudhuri et al 38 and our results are in agreement in that, as stated by Minton et al 2,[8][9][10][11][12] , the excluded volume plays an important role in the enzymatic reactions that take place in macromolecular crowded media. We have found that, at least in the case of the hydrolysis of N-succinyl-L-phenyl-Ala-p-nitroanilide catalyzed by alpha-chymotrypsin, the total volume excluded by the crowding agents has a greater impact on the velocity of the reaction than the size of these agents.…”
Section: Resultssupporting
confidence: 94%
“…As a result of increased viscosity, crowding is expected to decrease the rate of a diffusion-limited reaction, where the overall rate of the reaction is limited by the encounter of the reactants. For instance, the enzymatic activity of alkaline phosphatase [67], urease [20], pyruvate decarboxylase [20] and glutamate decarboxylase [20] has been reported to decrease as a function of polymeric crowding agent concentration, due to reduction in the rate of enzyme-substrate encounter. Furthermore, an increase in K m of EcoRV [68], mitochondrial creatine kinase [69] and α-chymotrypsin [70] in the presence of increasing polymeric crowder concentration has been suggested to result from an increased diffusion resistance in the sample.…”
Section: Viscositymentioning
confidence: 99%
“…However, after the pioneering work of Laurent in 1971 [21], quite a few studies have explored the effects of crowding on enzyme catalysis, even in vitro [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the effects of crowding on enzyme catalysis have been explored by different experimental works, excellently depicted by Zhou et al [16] and Noris and Malys [30]. Some of the studies present distinct effects produced by various crowding agents on the enzymes kinetics [26,33,[38][39]66]. These effects are given by different experimental conditions considering the type, shape, size and excluded volume of the used crowders.…”
mentioning
confidence: 99%